HUBUNGAN LAMA TERPAPAR SINAR LAS DENGAN KEJADIAN KONJUNGTIVITIS FOTOELEKTRIK DI PT. BINTANG INTI PERSADA SHIPYARD BATAM - Ibrahim .; Nurul Widiati (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2019)
Welding work which results in conjunctivitis is highly related to occupational health and safety science. Based on Outpatient Visits in all Hospitals in Riau Islands Province in 2019, 1767 outpatient visits were found with Conjunctivitis as well as other visiting disorders. Conjunctivitis in welding workers can occur due to factors such as the length of time a worker is exposed to welding light. The duration of exposure can cause an unsafe situation on the body especially on the eyes, which can cause photoelectric conjunctivitis. So the researchers wanted to find a long association with exposure to welding rays with the incidence of photoelectric conjunctivitis. This research method was observational analytic with a cross-sectional approach conducted at PT. Bintang Inti Persada Shipyard Batam City. The sampling technique is total sampling with a population of 48 workers in 2019 and obtained the results of 48 workers determined by inclusion and exclusion criteria. The results of the study were analyzed by frequency distribution in cross-tabulation then tested by Chi-square. The results of this study found workers who were exposed to welding light less than 4 hours a day and did not experience conjunctivitis as many as 16 (69.5%) workers, then in workers who were exposed to welding light less than 4 hours a day and experienced conjunctivitis as much as 7 ( 30.5%) workers. Whereas workers who were exposed to welding rays more than or equal to 4 hours a day and did not experience conjunctivitis were 6 (24%) workers, then workers who were exposed to welding rays more than or equal to 4 hours a day and experienced conjunctivitis as many as 19 (76 %) workers. From the analysis results obtained p = 0.002 with a significance level (Î±) â‰¤ 5% (0.05). So it can be concluded that there is a significant relationship between the length of exposure to welding rays with the occurrence of conjunctivitis. Conclusions: Based on this study it can be concluded that there is a significant relationship between the length of exposure to welding rays with the incidence of photoelectric conjunctivitis at PT. Bintang Inti Persada Shipyard in 2019